2005
DOI: 10.1124/jpet.105.084608
|View full text |Cite
|
Sign up to set email alerts
|

Acetoacetate Induces CYP2E1 Protein and Suppresses CYP2E1 mRNA in Primary Cultured Rat Hepatocytes

Abstract: The ketone body acetoacetate (AA) in the absence of insulin or in the presence of diabetic insulin levels decreases CYP2E1 mRNA expression in a concentration-and time-dependent manner in primary cultured rat hepatocytes. AA activates p70 ribosomal S6 kinase (p70S6K) and protein kinase C (PKC) by ϳ2-to 2.5-fold, respectively, following 6-h treatment. The AAmediated activation of p70S6K, but not PKC, was abolished by inhibition of PI 3-K with LY294002 [2-(4-morpholinyl)-8-phenyl-4H-1-benzopyran-4-one] or wortman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
(61 reference statements)
1
28
0
Order By: Relevance
“…16). In addition, our results also suggest that mTOR and downstream p70S6 kinase may effect AA-mediated inhibition of CYP2E1 mRNA expression (Abdelmegeed et al, 2005). In contrast, neither p38 MAPK nor ERK signaling pathways appear to play an active role in mediating the downregulation of CYP2E1 mRNA levels by AA as shown by the use of the MEK inhibitor PD98059 and the p38 MAPK inhibitor SB202190.…”
Section: Cytochrome P450mentioning
confidence: 54%
See 2 more Smart Citations
“…16). In addition, our results also suggest that mTOR and downstream p70S6 kinase may effect AA-mediated inhibition of CYP2E1 mRNA expression (Abdelmegeed et al, 2005). In contrast, neither p38 MAPK nor ERK signaling pathways appear to play an active role in mediating the downregulation of CYP2E1 mRNA levels by AA as shown by the use of the MEK inhibitor PD98059 and the p38 MAPK inhibitor SB202190.…”
Section: Cytochrome P450mentioning
confidence: 54%
“…Although AA decreased CYP2E1 mRNA, it significantly increased CYP2E1 protein levels which appears to be associated with increased mRNA translation and may reflect activation of eIF4E/4E-BP1 phosphorylation, as well as activation of the p70S6 kinase. This is supported in part, by the inhibitory effect of rapamycin, and inhibitor of mTOR, on AAmediated downregulation of CYP2E1 expression (Abdelmegeed et al, 2005).…”
Section: Cytochrome P450mentioning
confidence: 87%
See 1 more Smart Citation
“…Some hepatic cytochrome P450 isozymes of diabetic rats were reversed or partly reversed to the level of the controls after insulin treatment (Yamazoe et al, 1989). It has been reported that insulin and ketone bodies participated in the regulation of hepatic CYP2E1 in diabetic rats (Woodcroft et al, 2002;Abdelmegeed et al, 2005). However, the mechanisms involved in the regulation of CYP3A in liver and intestine by diabetes mellitus were not reported and need to be further investigated.…”
Section: Discussionmentioning
confidence: 87%
“…The activity and expression of hepatic Cyp3a in DM rats were associated with HOMA-IR, which suggests that insulin resistance or relative insufficiency of insulin may explain the affecting expression and activity of hepatic Cyp3a. Several reports have demonstrated that insulin and ketone bodies participating in the regulation of cytochrome P450 isozymes in the liver of DM rats and insulin treatment reversed or partially reversed alteration induced by diabetes [17,[37][38][39] . The elevated total serum cholesterol and triglyceride levels in DM rats were consistent with the increases in activity and expression of hepatic Cyp3a, suggesting that high cholesterol and triglyceride levels may explain inducing Cyp3a expression and activity.…”
Section: Discussionmentioning
confidence: 99%